2008
DOI: 10.1007/s00431-008-0811-1
|View full text |Cite
|
Sign up to set email alerts
|

Internet use and misuse: a multivariate regression analysis of the predictive factors of internet use among Greek adolescents

Abstract: The internet is an integral tool for information, communication, and entertainment among adolescents. As adolescents devote increasing amounts of time to utilizing the internet, the risk for adopting excessive and pathological internet use is inherent. The study objectives include assessing the characteristics and predictors of excessive internet use and evaluating the prevalence of pathological internet use among Greek adolescents. A cross-sectional study design was applied to this effect. The study populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
91
1
11

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(117 citation statements)
references
References 37 publications
11
91
1
11
Order By: Relevance
“…With respect to gender, male participants seem to exceed time of Internet use ≥ 4hrs/day and this is again on the same line as the findings of other studies (Morahan-Martin & Schumacher, 2000;Tsitsika et al, 2009). The Pew Internet and American Life Project (2000) reports in details how women's use of the Internet differs significantly from that of men while Boneva, Kraut, and Frohlich (2001) by studying in depth this dimension, showed that gender and the roles associated with it influences the amount and type of Internet use and the satisfaction gained from that use.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…With respect to gender, male participants seem to exceed time of Internet use ≥ 4hrs/day and this is again on the same line as the findings of other studies (Morahan-Martin & Schumacher, 2000;Tsitsika et al, 2009). The Pew Internet and American Life Project (2000) reports in details how women's use of the Internet differs significantly from that of men while Boneva, Kraut, and Frohlich (2001) by studying in depth this dimension, showed that gender and the roles associated with it influences the amount and type of Internet use and the satisfaction gained from that use.…”
Section: Discussionsupporting
confidence: 88%
“…With regard to Greek adolescents it appears to be on the same line as shown in the study of Tsitsika et al (2009) in Greece where the prevalence of 1.00% reported addictive Internet use while borderline Internet use among the study population was 12.8%.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The control group consisted of children who are occasional Internet users who represent the current norm of Internet use of schoolchildren and adolescents of Internet use over the prior 30 days was categorized according to consensus of previous reports [7][8][9].…”
Section: Methodsmentioning
confidence: 99%
“…The rate of problematic Internet use in Italian adolescents was 5.4% (22). The prevalence of borderline Internet use in Greek adolescents was 12.8%, while 10.4% of male excessive Internet users reported addictive Internet use (23). Using the Pathological Internet Use (PIU) scale in British students, 18.3% were considered to be pathological Internet users (24).…”
Section: Diagnosis and Prevalencementioning
confidence: 99%